Bibliography: the Conflict in Yemen - Teiner, David (Perspectives on terrorism, 2022)
This bibliography contains books, edited volumes, journal articles, book chapters, theses, grey literature, and other resources on the ongoing conflict in Yemen. It mainly features publications analyzing the Houthi insurgency, the Saudi-led military intervention, and war-related implications for the Yemeni population, regarding lacking basic social services and an ever more unfolding medical crisis as well as famine. Literature on Yemeni cultural life, religion, and economy were included when promising to enhance understanding of the long-lasting conflict.